The Effect of Emotional Intelligence on College Adjustment Among Foundation 1 and Foundation 2 Kolej PERMATA Insan Students - Nor Raihan Zulkefly; Noor Farina Febra; Nur Nabila Insyirah Ahmad Mahyuddin; Nur Humairah Mohd Rais; Ainul Mardhiyah Mohd Rais (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan